Three-Track Detection Using a Multilayer Perceptron for Dual-Layer Bit-Patterned Magnetic Recording Systems - Santi Koonkarnkhai; Siriphon Plotchu; Warunee Martnok; Natthakan Rueangnetr; Sathapath Kilaso; Piya Kovintavewat; Chanon Warisarn (IEEE Transactions on Magnetics, 2025)
This paper proposes a multilayer perceptron (MLP)-based three-track detection method for dual-layer bit-patterned magnetic recording (BPMR) systems. Three different MLP architectures are explored and evaluated, namely, 1) a single MLP detecting all three tracks simultaneously, 2) three MLPs, each detecting one track independently, and 3) two MLPs dedicated to upper and lower recording layers. Simulation results show that the proposed MLP-based systems outperform the conventional partial-response maximum-likelihood detection scheme, particularly under severe interferences and high areal density. Among the proposed systems, the two-MLP architecture offers the optimal balance between detection accuracy and computational complexity, making it the most promising solution for future high-density magnetic recording systems.
Keywords: Neural Networks and Applications; Blind Source Separation Techniques